Advocates’ strategies for resolving muslim family conflicts through mediation: An islamic religious education approach - Aris Widodo; Husna Nashihin; Joni (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2024)
This study employs a qualitative descriptive approach. Data were collected through interviews, observation, and documentation involving mediators and relevant stakeholders at the Sleman Religious Court. The analysis focuses on mediation strategies applied by non-judge mediators and the factors influencing the success of mediation in Muslim family disputes. The findings reveal that mediation strategies implemented by non-judge mediators include religious, psychological, nostalgic, family-based, and logical-mathematical approaches. These strategies are used flexibly depending on the characteristics of the disputing parties. The success of mediation is influenced by internal factors such as the willingness of the parties, communication skills, mediator competence, and case complexity, as well as external factors such as social support and cultural pressures. Mediation outcomes vary from unsuccessful settlement, partial agreement (amicable divorce with mutual arrangements), to full reconciliation resulting in case withdrawal. In conclusion, PERMA No. 1 of 2016 strengthens the role of mediation as a mandatory and strategic mechanism in civil dispute resolution. Mediation at the Sleman Religious Court not only contributes to legal efficiency but also reflects values of Islamic Religious Education such as deliberation (musyawarah), reconciliation (islah), and moral responsibility in resolving Muslim family conflicts.